Applied general systems research. Recent developments and trends. Proceedings of a NATO International Conference on Systems Science, held in Binghamton, New York, August 15-19, 1977 (Angewandte allgemeine Systemforschung). - (:unkn) unknown (My University, 1978)
Übersicht mit besonderer Betonung auf Anwendungsmöglichkeiten auf den Gebieten Biologie und Sozialwissenschaften.
Keywords: Systemanalyse; Systemforschung; Systemwissenschaft; Biologie; Sozialwissenschaft